Antibacterial Activity Test of Ag Nanoparticle Soap Turi Leaf Extract (Sesbania grandiflora) Against Staphylococcus aureus Bacteria - Rusiana, Della Ayu; Tivani, Inur (Universitas Negeri Medan, 2024)
Silver metal nanoparticles have biocidal properties as a non-toxic inorganic antibacterial agent. Flavonoid compounds from the Turi Leaf (Sesbania grandiflora) plant extract as a natural bio reductant. In the research, UV-Vis spectrophotometric testing parameters and antibacterial soap preparations were carried out. Synthesis and Characteristics of Silver Nanoparticles were carried out, with soap preparations made into 3 formulas with different variations in Agno3 concentration, namely 1 mM, 2 mM, and 3 mM and antibacterial activity tested using well diffusion. The results of the absorption spectrum of Ag nanoparticles show the highest peak at a value of 280-290 nm. In the antibacterial activity test, the greater the AgNO3 concentration in the Ag nanoparticle soap, the greater the inhibition zone created by Staphylococcus aureus bacteria. The optimum concentration in soap preparations is 3 mM producing a wavelength of 300 nm with an absorbance value of 1.105. In terms of antibacterial activity, the most effective way to inhibit the growth of Staphylococcus aureus bacteria is formulation III, with an inhibitory power of 7.69 cm2 .